1996
DOI: 10.1111/j.1432-1033.1996.0707h.x
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of Clostridium Difficile Toxin‐B‐Inhibited Phospholipase D by Phosphatidylinositol 4,5‐Bisphosphate

Abstract: Receptor signalling to phospholipase D (PLD) in human embryonic kidney (HEK) cells stably expressing the m3 muscarinic acetylcholine receptor apparently involves Rho proteins. Since phosphatidylinositol 4,5-bisphosphate [PtdIns(4,5)P2] has been recognized as an essential cofactor for PLD activity and since activated Rho proteins have been reported to stimulate the synthesis of PtdIns(4,5)P2, we studied whether in HEK cells PLD activity is regulated by PtdIns(4,5)P2 and, in particular, whether PtdIns(4,5)P2 can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(64 citation statements)
references
References 30 publications
1
61
0
Order By: Relevance
“…Rho regulates the formation of actin stress fibers and focal adhesions (23,24) and has also been implicated in the regulation of phosphatidylinositol 3-kinase (25) and phosphatidylinositol 4-phosphate 5Ј-kinase (26), which synthesize PIP 3 and PIP 2 , respectively. Although the present and previous (30) findings indicate that Rho can directly activate PLD, the possibility that the G protein exerts part of its stimulatory effects on PLD in vivo through alterations in PIP 2 is suggested by the findings of Jakobs and co-workers (47). Irrespective of the mechanisms by which Rho regulates PLD, there is growing evidence that this protein plays a role in coupling cell surface receptors to PLD activation and other cellular responses (22,48).…”
Section: Pkc-␣ and -␤Ii Phosphorylate Rpld1 In Vitro-although The Resmentioning
confidence: 82%
“…Rho regulates the formation of actin stress fibers and focal adhesions (23,24) and has also been implicated in the regulation of phosphatidylinositol 3-kinase (25) and phosphatidylinositol 4-phosphate 5Ј-kinase (26), which synthesize PIP 3 and PIP 2 , respectively. Although the present and previous (30) findings indicate that Rho can directly activate PLD, the possibility that the G protein exerts part of its stimulatory effects on PLD in vivo through alterations in PIP 2 is suggested by the findings of Jakobs and co-workers (47). Irrespective of the mechanisms by which Rho regulates PLD, there is growing evidence that this protein plays a role in coupling cell surface receptors to PLD activation and other cellular responses (22,48).…”
Section: Pkc-␣ and -␤Ii Phosphorylate Rpld1 In Vitro-although The Resmentioning
confidence: 82%
“…Large clostridial toxins, such as Clostridium difficile toxin B and toxin A, also block PLD activity induced by PMA, or GTP [S] in vitro, probably by reducing PI4-P 5-kinase activity and decreasing PIP 2 level (Schmidt et al, 1996a;Rümenapp et al, 1998). Indeed, PLD, which contains a PH (pleckstrin homology) domain and a PX (Phox homology) domain, as well as binding sites for phospholipids, has been reported to anchor to PIP 2 where it is close to its substrates (Frohman and Morris, 1999).…”
Section: Toxins That Modulate Host Pld Activity Via Small Gtpasesmentioning
confidence: 99%
“…Studies on the mechanisms of PLD inhibition by Clostridium difficile toxin B and C. botulinum C3 exoenzyme, which inactivate Rho family GTPases [24], indicated that these toxins decrease the cellular level of PtdIns(4,5)P # [25,26]. As receptor stimulation of PLD activity in HEK-293 cells additionally involves a tyrosine-kinase-dependent mechanism [27], as reported similarly for other cell types [28,29], we have examined in this study whether the cellular level of PtdIns(4,5)P # is under the control of tyrosine phosphorylation.…”
Section: Introductionmentioning
confidence: 99%
“…Pervanadate (10 mM stock solution) was produced from a combination of 20 mM H # O # and 20 mM orthovanadate, and allowed to stand at room temperature for at least 15 min. All other materials were from sources described previously [22,26,27].…”
Section: Introductionmentioning
confidence: 99%